PENGARUH TEGANGAN AIR TERHADAP EFISIENSI PEMUPUKAN N, P, DAN K PADA TANAMAN PADI GOGO LOKAL VARIETAS KALPATALI (Oryza sativa L.) DI TANAH ULTISOL - Pratama, Andika; Idwar, Idwar; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research is held at the greenhouse of Faculty of Agriculture, University of Riau, Pekanbaru starts in  March to August 2016. The trial uses the factorial of Complete Random Program (RAL). The first factor of the water tension comprises of three levels, they are : (pF 1 - 1,97), (pF 2,29 - 2,54) and (pF 2,70 - 3) and the second factor of the fertilization dosage of  N, P, and K which comprises of four levels without fertilization of N, P, and K, given ½ x recommended dosage, given recommended dosage, and given 1½ x recommended dosage. The process is repeated three times. The data of observation result could be statistically analysed with ANOVA and followed by Duncan test at 5% level. The observed parametre are nutrients uptake of N, P and K, the efficiency of absorption of N, P, and K, height of plants, phase of malai's appearances, number of productive tiller, ratio of stem and root,  period of harvest, weight of 1000 paddy seeds and product efficiency. The result of this research shows the interaction of water tension and fertilisation dosage of N, P, and K visibly influnce the nutrients of N, P, and K, height of plants,  ratio of stem and root, and weight of 1000 paddy seeds. Invisibly influence to the phase of malai's appearances, period of harvest, and number of productive tiller. Combination of  water tension  pF 1 - 1,97 and fertilization dosage 1 ½ x recommeded dosage are the best combinations.Keywords: N P and K fertilizer, efficient fertilization, gogo local rice, water  tension, Ultisol